A proof-of principal study using phase-contrast imaging for the detection of large airway pathologies after lung transplantation - Umkehrer, Stephan; Morrone, Carmela; Dinkel, Julien; Aigner, Laura; Reiser, Maximilian F.; Herzen, Julia; Yildirim, Ali Ö; Pfeiffer, Franz; Abbasi Dezfouli, Katharina (Scientific reports, 2020)
In this study we aim to evaluate the assessment of bronchial pathologies in a murine model of lung transplantation with grating-based X-ray interferometry in vivo. Imaging was performed using a dedicated grating-based small-animal X-ray dark-field and phase-contrast scanner. While the contrast modality of the dark-field signal already showed several promising applications for diagnosing various types of pulmonary diseases, the phase-shifting contrast mechanism of the phase contrast has not yet been evaluated in vivo. For this purpose, qualitative analysis of phase-contrast images was performed and revealed pathologies due to previous lung transplantation, such as unilateral bronchial stenosis or bronchial truncation. Dependent lung parenchyma showed a strong loss in dark-field and absorption signal intensity, possibly caused by several post transplantational pathologies such as atelectasis, pleural effusion, or pulmonary infiltrates. With this study, we are able to show that bronchial pathologies can be visualized in vivo using conventional X-ray imaging when phase-contrast information is analysed. Absorption and dark-field images can be used to quantify the severity of lack of ventilation in the affected lung.
Gesehen am 06.05.2021